Atividade judiciária como alternativa de combate à criminalidade: uma investigação para os municípios cearenses - Oliveira, Denise Xavier Araújo de (2013)
Using a recent database on productivity of judges Ceará, this study follows the proposal of Becker (1968) and proposes a model to investigate the determinants of crime in an empirical exercise for the municipalities of the state of Ceará. The proposed models confront variables of economic development, agility and efficiency in judicial cases of illicit activity. The approach dealt with criminal activity according to the classification adopted in the Brazilian Penal Code, which is based on the legal injured: the person or property. Robust estimates confirm the beneficial effect of agility and efficiency of the judicial system in reducing criminal behavior, although evidencing a positive relationship between municipal development and torts. Together, this evidence suggests that public managers, besides of making strenuous efforts and resources on the intensification of surveillance and apprehension of criminals, as well as the improvement of social conditions, especially education, yet consider developing public policies that allow optimize investigation and punishment crimes.